Quelques aspects de la production céramique à la lumière des sources écrites ou comment pratiquer l’archéologie médiévale - Jean Chapelot (Archéologie Médiévale)
A concensus exists among many medieval archaeologists concerning written sources : they are rare, if not non existent on many of the subjects that interest them and what’s more, they are difficult to find. This opinion comforts an equally widespread notion ; that of archaeology seen as an independent research field, particularly relative to history or art history. Three examples show, with regards to pottery, how the medieval archaeologist must also unquestionably be a historian and know how to utilize written sources. The first concerns the origins of pottery production in the Chapelle-des-Pots village in Charente, where this activity is know from archaeological sources from the thirteenth century onwards. The written sources inform that the present day eighteenth century church was preceded by a Norman edifice. This leads us to rethink the history of the pottery production by showing that the craftsman were above all established outside of the village centre during the thirteenth and fourteenth centuries, then within the centre after the Middle Ages. The second example approaches the problem of the statute of a family from Genouillé (Sarthe) that pays tribute during the fifteenth century to the lord of that vicinity for his right to extract clay, which leads us to reflect upon the origins of this activity in the parish before this date, and its history after the Middle Ages. The third example sheds light on the relationship between terra cotta craftwork and the market economy via the supply of sugar moulds to the refiners of the town of La Rochelle. Two contracts show that these specialised moulds are produced in the second half of the sixteenth century in the rural workshops of Medieval origin on the specific demand of the Rochelais refiners. These examples are intended to illustrate three essential points that characterise archaeology of the Middle Ages: written sources are often the best means of establishing an archaeological problematic, their use sheds light on archaeological data by providing complementary, sometimes even original approaches, as these often concern aspects that do not interest the classical historian, they can only be investigated and capitalized on by archaeologists, and they only represent their full value when compared to archaeological data.